Triazatruxene based covalent organic framework and its quick-response fluorescence-on nature towards electron rich arenes - Xie, Yun-Feng; Ding, San-Yuan; Liu, Jun-Min; Wang, Wei; Zheng, Qi-Yu (Journal of materials chemistry. C, Materials for optical and electronic devices, 2015)
Two new 2D covalent organic frameworks (COFs) with a regular honeycomb lattice, TAT-COF-1 and TAT-COF-2, were synthesized based on triazatruxene derivatives. The two COFs, especially TAT-COF-2, have a large BET surface area, good crystallinity, moderate to good hydrogen and carbon dioxide adsorption abilities and also possess good CO 2 /N 2 selectivity. When suspended in ethanol, the fluorescence of TAT-COF-2 could be enhanced or quenched by different solvents. It also shows a rapid fluorescence-on and fluorescence-off nature towards electron rich and deficient arene vapors, respectively. After being exposed to electron-rich arene vapors, the enhanced fluorescence intensity can be recovered to normal level after 5 minutes in an ambient atmosphere, which means the sample could be reused conveniently for detecting electron rich arene vapors.